2013
DOI: 10.1371/journal.pone.0079873
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Effects of Ramadan Fasting and Time-Of-Day on Apolipoprotein AI, B, Lp-a and Homocysteine Responses during Aerobic Exercise in Tunisian Soccer Players

Abstract: ObjectiveTo examine the time-of-day and Ramadan fasting (RF) effects on serum apolipoprotein-AI (Apo-AI) and B (Apo-B), lipoprotein particles-a (Lp-a), high-sensitive C-reactive-protein (hs-CRP), and homocysteine (Hcy) during the Yo-Yo intermittent recovery test (YYIRT).DesignPerformance and biochemical measures were completed at two times-of-day (07:00 and 17:00 h), 1-week before RF (BR), the second week of RF (SWR), and the fourth week of RF (ER).SettingFor each session, subjects performed the YYIRT, and blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(70 citation statements)
references
References 36 publications
2
67
0
1
Order By: Relevance
“…Therefore, the diurnal variation of performance was confirmed, but the reason of the varied diurnal performance has remained unclear. Possible explanation may be that this improvement in performance in the evening might be associated with energy system distribution during the YYIRT test (19), an intermittent cycling exercise (36), repeated-sprint test (33), and 5 × 6 s repeated sprint cycling (21). These results suggest that this improvement in the evening is not caused by the alteration in a unique energy system (i.e., aerobic or anaerobic) (15,17,19).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Therefore, the diurnal variation of performance was confirmed, but the reason of the varied diurnal performance has remained unclear. Possible explanation may be that this improvement in performance in the evening might be associated with energy system distribution during the YYIRT test (19), an intermittent cycling exercise (36), repeated-sprint test (33), and 5 × 6 s repeated sprint cycling (21). These results suggest that this improvement in the evening is not caused by the alteration in a unique energy system (i.e., aerobic or anaerobic) (15,17,19).…”
Section: Discussionmentioning
confidence: 88%
“…Participants are strongly encouraged verbally throughout the test. All subjects carried out a warm-up period consisting of the first four running bouts in the test (19). The participants perform the test in the same condition (i.e., comfortable sports shoes and appropriate sports clothing).…”
Section: Exercise Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have confirmed that IF decreases serum lowdensity lipoprotein (LDL), a major protein component of LDL cholesterol, and also decreases total cholesterol, triglycerides, and high-density lipoprotein cholesterol levels [112]. Moreover, certain evidence suggests that after 3 weeks of alternate-day fasting, body fat and insulin levels decrease [113].…”
Section: Effects On Biochemical Parameters: Insulinmentioning
confidence: 99%
“…¿Qué factores influyen en la carga física de un partido de fútbol Estas variables situacionales parecen tener una influencia en el comportamiento físico de los equipos durante los partidos y no parecen estar asociadas con el nivel de condición física de los jugadores (Castellano et al, 2011). Algunas de estas variables hacen referencia a la posición del jugador en el campo (Bradley et al, 2011), nivel de oposición (Hammouda et al, 2013), la localización geográfica del partido, jugar de local o visitante (Almeida, Ferreira, & Volossovitch, 2014), la categoría competitiva (Rampinini, Impellizzeri, Castagna, Coutts, & Wisløff, 2009), la temperatura (Mohr et al, 2010) o el horario del partido (Chtourou et al, 2012) entre otras.…”
Section: Introductionunclassified